Study on the Safety Thickness of Rock Strata for Outburst Prevention in Deep Tunnel Based on Numerical Modeling and Backpropagation Neural Network. (27th February 2023) - Cao, Zhensheng; Liu, Jiazhu; Zhang, Shaoqiang; Li, Bowen; Zhang, Zhenhu; Wang, Zhongjie; Jiang, ChenChen
Abstract : Water inrush and mud inrush pose a serious threat to safe construction in underground engineering, but it is very difficult to determine the safe distance of outburst prevention rock mass. Based on deep-buried tunnel engineering, this paper proposes a method to determine the safe distance from water inrush disaster between the tunnel and the fault fracture zone. This method combines numerical modeling and backpropagation (BP) neural network. By means of numerical simulation, the internal influence law of the water pressure, lateral pressure coefficient, fault fracture zone width, and tunnel burial depth on the surrounding rock is analyzed. The evolution law of the minimum safe strata thickness under a single variable and the correlation degree between minimum safe strata thickness and various disaster factors are revealed. Based on the BP neural network analysis of the simulation results and the measured data of Wulaofeng Tunnel, the calculated values of safe strata thicknesses of fault fracture zone (F10) were determined. The results show that the thickness of the safe rock strata increases with increasing water pressure, lateral pressure coefficient, fault fracture zone width, and tunnel burial depth. The minimum safe thickness of F10 of the tunnel ranges from 7.1 m to 7.4 m, and 10 m is reserved in the actual project. The calculated results are consistent with the reserved thickness value in the construction. This conclusion can provide a reference for similar projects.